Teoreticeskie i metodologiceskie osnovy finansirovanija fiziceskoj kul'tury i sporta - Pokrovskaja, L. D. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The deterioration of the condition of the social health that conducts to significant labour losses is observed within the last decade. It is imposes the additional economic burden on the State as the increase of charges in the social area and undermines its defensibility. All that causes the need for the development of actions for the strengthening of the society health and searching of ways of the initial and the secondary prophylaxis of diseases. It is very urgent, that the development of mass physical culture and sports become one of the effective tools of the improvement of the society health throught the state policy in this direction. The close interaction and the coordination of the efforts in the area of the development of physical culture and sports with other ministries and the departments interested in the strengthening of social health is needed also.